TUNTUTAN KINERJA DALAM KETERANCAMAN KERJA: DILEMA KARIR PENYULUH AGAMA NON PEGAWAI NEGERI SIPIL - Sifatul Aliyah; Bayu Mitra A. Kusuma (JURNAL ILMIAH SYI'AR, 2019)
Religious counselors are the spearhead profession in the spread of religion while representing the government in delivering religious and development programs in the national and local level. They are not only consist of civil servants (PNS) employees, but also non-civil servants (non-PNS) employees. For those who already have PNS status, their careers are generally more certain and in a safe position. On the contrary, for those with non-PNS status, they are in a dilemma. On the one hand, their existence really has important meaning in the midst of the rise of various religious issues. But on the other hand, they are in a stagnant career condition, there is no career certainty and lack of attention compared to the PNS. Therefore, basically it is necessary to empower non-PNS religious counselor. The research result shows that the government through the Ministry of Religious Affairs actively has attempted to empower non-PNS religious counselor with the Islamic Information Information Management System and the E-PAI application. In addition the government has made efforts such as training and coaching, examining performance reports, making clear guidelines or regulations, and upgrading the salary up to 100 percent. The research method used in this study is descriptive qualitative type and emphasizes on the study of literature.